A social psychological approach to mission assessment - Matteo, Elizabeth K. (Journal of management, spirituality & religion, 2015)
Using a social psychological framework, this study examined the relationship between undergraduates' sense of school belonging and endorsement of their universities' mission identity at two US universities of different size, geographic location, and Catholic traditions. Undergraduates at both universities completed online surveys that included: demographic information, the DePaul Mission and Values Inventory, and the School Sense of Community Scale. Findings revealed significant correlations between students' sense of school belonging and their endorsement of the religious pluralism and innovation aspects of the mission identities at both institutions. The connection between students' psychological need to belong and their endorsement of their campuses' religious identity was discussed in terms of higher education planning and assessment.